Effectiveness of Customer Relationship Management (CRM) towards enhancing customer loyalty in Epic Evolution (M) Sdn Bhd, Johor / Lily Suryana Roslaili - Roslaili, Lily Suryana (Faculty of Business and Management, 2011)
Customer relationship management (CRM) is the overall process of building and maintaining profitability customers’ relationship by delivering superior customer value and satisfaction. CRM will give many advantages to the company and the main advantage is to enhance customer loyalty in the company. Besides that, CRM indirectly will increase profitability in company.